A Case of Ostraceous Psoriasis with Psoriatic Arthritis in an AIDS Patient - Park, Minkee (Indian J Dermatol, 2018)
Human immunodeficiency virus (HIV) infection may present with severe and atypical cutaneous diseases. Psoriasis also can develop in HIV patients associated with immune dysfunction and be presented as more severe and atypical manifestation. Furthermore, treatment of psoriasis in HIV patients can be complex and challenging. Herein, we report the case of a 50-year-old male with a 9-year history of HIV infection who developed an uncommon clinical variant of psoriasis with psoriatic arthritis and we discuss a possible pathogenesis of this autoimmune disease and possible treatment.